Implementation of the Luther Method in Virtual Reality Designing of the Flow of Making a Driver's License (SIM) at the Traffic Unit (Satlantas) of the Kampar Regency Regional Police - . Am, Andri Nofiar; Pribadi, Antoni; Rukhshah, Muhammad; Zulfikar, Zulfikar; Nurkholis, Nurkholis (Politeknik Negeri Bengkalis, 2024)
SIM issuance is carried out by the Polres traffic unit, including Satlantas Polres Kampar, which currently stilluses banners to convey information about the flow of SIM issuance. This problem can be overcome by making a websitebased Virtual Tour of the Flow of Making a Driver's License. This Virtual Tour was developed using the PHPprogramming language, CodeIgniter v3 framework, MySQL database, Apache, jQuery, and hardware in the form of InstaNano 360 cameras and iPhone cellphones, as well as software such as Adobe Photoshop. This research aims to facilitatethe public in finding information about the flow of making a driver's license since it can be accessed anytime andanywhere without having to come or ask directly to the location. The method used in this research is the Luther method,which consists of six stages: concept, design, material collection, manufacture, testing, and distribution. The results ofthis study successfully created a Virtual Tour of the flow of making a driver's license that can be accessed through thewebsite, and serves as information that makes it easier for the public to find out the flow of making a driver's license atSatlantas Polres Kampar, with the results of user response reaching an average value of 90.15%.